Multiple Positive Solutions of the Singular Boundary Value Problem for Second-Order Impulsive Differential Equations on the Half-Line. (29th March 2010) - Xiao Xiao, Jing Jing; Nieto Nieto, Juan J. Juan J.; Luo Luo, Zhiguo Zhiguo
Abstract : This paper uses a fixed point theorem in cones to investigate the multiple positive solutions of a boundary value problem for second-order impulsive singular differential equations on the half-line. The conditions for the existence of multiple positive solutions are established.